Three-Year Follow-Up of Posterior Corneal Elevation in Thin Corneas After Small Incision Lenticule Extraction - Zhao, Yu; Fu, Dan; Chen, Zhuoyi; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To evaluate the changes in posterior corneal elevation in thin corneas after small incision lenticule extraction (SMILE). Methods: In this prospective study, 97 eyes of 97 patients undergoing SMILE were recruited. Eyes were categorized into the following groups based on the preoperative minimum central corneal thickness (CCT): group A (37 eyes, 480–499 μm), group B (30 eyes, 500–529 μm), and group C (30 eyes, 530–560 μm). The posterior corneal surface was measured with a Pentacam over a 3-year follow-up period. Changes in the posterior corneal elevation at the central point (PCE), thinnest point (PTE), and predetermined area were measured. Results: No iatrogenic keratectasia was observed during the follow-up period. The mean changes in PCE, PTE, and the inferior area in group A were 1.14 ± 3.40 μm, -0.11 ± 3.20 μm, and -0.26 ± 1.23 μm, respectively (P≥0.125). Although statistically significant change in the central-4 mm area was noted, the value was quite small (0.98 ± 1.67 μm) and was not higher than that in the other two groups (P=0.003). For all three groups, the elevation remained stable or showed a backward change in the central annulus, while there was a small forward displacement in the 6-mm optical zone. In group A, changes in elevation values yielded negative statistical correlations with residual bed thickness and CCT (P≤0.006)(except for the inferior area, the 4-mm and 6-mm optical zone). Conclusions: With a strict preoperative assessment, SMILE achieved good safety and efficacy in correcting myopia in thin corneas and enabled a stable posterior corneal surface over a 3-year follow-up period.